Mitigating Candida auris at a Busy Community Hospital: A Quasi-Experimental Near Real-Time Approach. (4th October 2017) - Lesho, Emil; Bronstein, Melissa; McNamara, Jodi; Callahan, Megan; Kwak, Yoon; Campbell, Jean; Vargas, Roberto L; Hinkle, Mary; Walsh, Edward
Abstract: Background: Candida auris, an emerging multidrug-resistant pathogen associated with increased mortality, can disseminate on hospital surfaces and resist disinfection. Transmission dynamics remain poorly understood at community hospitals. Immediately following identification of a C. auris infection in an unsuspected patient admitted to a semi-private room 6 days previously, we sought to limit and determine the extent of C. auris contamination at Rochester General (RG), a 528-bed hospital in New York, using available resources. Methods: The index and roommate were placed on enhanced contact precautions and moved to private rooms. Their former room was terminally cleaned with peracetic acid/hydrogen peroxide (PAHP) and UV light. Ten high-touch environmental surfaces in the new rooms of the index and roommate, the nursing stations, and throughout the ward were sampled immediately before and after, and between daily cleaning. The nares, axillae, and groin of the index, the roommate, and all concurrent ward patients were also sampled. All patients on the involved ward were sequentially moved from their initial rooms into vacated rooms that were terminally cleaned with PAHP and UV light. Prior to the index event, RG laboratory began sending all possible C. auris isolates to the state public health laboratory for confirmation, and using PAHP for all cleaning. RG also leverages preexisting agreements with other referral laboratories to support outbreak investigations. Hand-hygiene compliance averaged 80–90% on the ward. Hospital leaders, laboratory, nursing, environmental services, and local public health personnel regularly participate in infection prevention efforts. Results: C. auris was isolated from 3 of 132 surface samples on the eighth, nineth, and 15th day of ward occupancy, and 0 of 48 patient samples from 18 co-located patients. The index remained colonized until death on hospital Day 21. No surfaces were C. auris -positive 1 month later. Conclusion: Compared with prior reports, dissemination at RG was limited. This, the first such quantitative assessment, illustrates how community hospitals can enhance surveillance and patient safety when formal agreements, vigilance, and multi-disciplinary and interagency teamwork exist before outbreaks occur. Disclosures: All authors: No reported disclosures.